Evaluation Performance of Stock Portfolio Using The Risk Adjusted Performance Methods - Ema Sari; Syamsu Alam; Muhammad Sobarsyah (Magister Management, Hasanuddin University, 2022)
This study aims to determine the differences in performances of the LQ 45 stock portfolio using 3 different methods, which are Sharpe, Treynor, and Jensen from 2016 until 2020. The study applied a purposive sampling technique with certain criteria. Portfolio formation in this study uses a single index model. Each sample is measured by all conditions or periods, a one-way analysis of variance by rank with the method used that is the Kruskal-Wallish test. It is then tested whether the portfolio performance in each period will have a similar rank or not if measured by different methods. The test results with the Kruskal-Wallish test on the three methods obtained X2 = 0.004 with a probability of 0.998. With, this evaluation, the results indicate that there is no significant difference between the tests using the Sharpe, Treynor, and Jensen methods. Interestingly, Treynor shows consistent measurement than the other two methods.